Simultaneous determination of telmisartan and amlodipine in human plasma by LCâMS/MS and its application in a human pharmacokinetic study - Vasu Babu Ravi; Jaswanth Kumar Inamadugu; Nageswara Rao Pilli; Vudagandla Sreenivasulu; Venkateswarlu Ponneri (Elsevier, 2012)
A rapid and sensitive liquid chromatographyâtandem mass spectrometric (LCâMS/MS) assay method has been developed and fully validated for the simultaneous quantification of telmisartan and amlodipine in human plasma. Carbamazepine was used as an internal standard. Analytes and the internal standard were extracted from human plasma by solid-phase extraction technique using Waters OasisÂ® HLB 1Â cm3 (30Â mg) extraction cartridge. The reconstituted samples were chromatographed on a Hypurity advance C18 column (50Â mmÃ4.6Â mm, 5Â Î¼m) using a mixture of acetonitrileâ5Â mM ammonium acetate buffer (pH-4.0) (50:50, v/v) as the mobile phase at a flow rate of 0.8Â mL/min. The calibration curve obtained was linear (râ¥0.99) over the concentration range of 2.01â400.06Â ng/mL for telmisartan and 0.05â10.01Â ng/mL for amlodipine. Method validation was performed as per FDA guidelines and the results met the acceptance criteria. A run time of 2.5Â min for each sample made it possible to analyze more than 400 human plasma samples per day. The proposed method was found to be applicable to clinical studies. Keywords: Telmisartan, Amlodipine, Human plasma, Solid-phase extraction, LCâMS/MS, Pharmacokinetics